sqrt(14) * sqrt(28)
= sqrt(14) * sqrt(14*2)
= sqrt(14) * sqrt(14) * sqrt(2)
= 14 * sqrt(2)
Notice that I used two properties:
sqrt(a*b)=sqrt(a)*sqrt(b)
sqrt(a)*sqrt(a)=a
2006-12-23 12:37:48
·
answer #1
·
answered by Professor Maddie 4
·
5⤊
0⤋
Well the technical way society teaches you is to multiply the numbers underneath the sqrt and then find a perfect square factor to factor and then carry out the math.
The easy way, especially for this problem, is to first factor the numbers:
sqrt(14) is alright for now, though...
sqrt(28) can be written as: sqrt(2*14)
Now 'multiply'
sqrt(14*14*2)
Since there is a 14^2 you can just simplify that to 14*sqrt(2) or 14sqrt2
2006-12-23 20:40:58
·
answer #2
·
answered by AibohphobiA 4
·
3⤊
0⤋
â14 * â28
= â14 * â14*2
= â14 * â14 * â2
= 14â2
2006-12-23 23:10:32
·
answer #3
·
answered by M. Abuhelwa 5
·
0⤊
0⤋
You have to multiply BOTH square roots and then reduce the square roots.
We have:
sqrt(14) times sqrt{28} = sqrt{392}.
sqrt{392} can be reduced.
sqrt{392} = sqrt{49} times sqrt{8}
The sqrt{49} is a perfect square because 7 times 7 = 49.
So, sqrt{49} = 7..We will use this 7 later.
The sqrt{8} = sqrt{4} times sqrt{2}
The sqrt{4} is another perfect square and so it becomes 2. We now multiply this 2 by the 7 we found above. See it?
Multiply 7 times 2 = 14.
What about the sqrt{2}?
Final answer:
14(sqrt{2})
Guido
2006-12-23 21:46:41
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Simplify: sqrt 14 sqrt 28
sqrt 2 * sqrt 7 * 2 * sqrt 7
sqrt 2 * 2 * 7 (because sqrt 7 * sqrt 7 = 7)
14 * sqrt 2
2006-12-23 21:04:38
·
answer #5
·
answered by Piguy 4
·
2⤊
0⤋
â14*â28=â14*28=â14*14*2=14â2
2006-12-23 20:52:54
·
answer #6
·
answered by mu_do_in 3
·
2⤊
0⤋
well, sqrt(14) * sqrt(28) = sqrt(14*28)
28 = 14*2, so we can rewrite as sqrt(14*14*2)
since 14 is repeated twice, we can take it out while leaving the 2 in the square root. therefore, we get:
14 * sqrt(2)
2006-12-23 20:38:41
·
answer #7
·
answered by Anonymous
·
3⤊
1⤋
sqrt(14) * sqrt(28) = sqrt(14 * 28) = sqrt(14 * 14 * 2) = 14sqrt(2)
2006-12-23 21:34:40
·
answer #8
·
answered by Sherman81 6
·
0⤊
0⤋
You have sqrt14sqrt28
sqrt28 is like sqrt(14*2)---------------------1
sqrt(14*2) can also be ---> sqrt14sqrt2--------------2
therefore sqrt14sqrt28 can be sqrt14sqrt14sqrt2---------3
and sqrt14sqrt14 is ==14
hence getting 14sqrt2 as in eqn. 2 above
2006-12-23 21:20:11
·
answer #9
·
answered by jodesy 1
·
0⤊
0⤋
â14*â28
â14*â14*2
(â14*â14)*â2
14â2
2006-12-23 21:06:03
·
answer #10
·
answered by Anonymous
·
1⤊
0⤋